2023
DOI: 10.1029/2023wr034630
|View full text |Cite
|
Sign up to set email alerts
|

A Physics‐Aware Machine Learning‐Based Framework for Minimizing Prediction Uncertainty of Hydrological Models

Abstract: The availability of water resources is not uniform across different time and spatial scale. Therefore, effectively managing the available water resources is crucial for the wide range of applications such as irrigation, hydropower generation, flood, and drought management, etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 118 publications
(253 reference statements)
0
2
0
Order By: Relevance
“…The framework demonstrated consistent accuracy, especially for long lead time and low flow predictions. In a subsequent study [96], the authors evaluated different scenarios, such as using only weather data, only intermediate variables prediction intervals, only SFP intervals, or all these variables together. They found that simulations incorporating all variables outperformed the others consistently.…”
Section: Residual Error Modelingmentioning
confidence: 99%
“…The framework demonstrated consistent accuracy, especially for long lead time and low flow predictions. In a subsequent study [96], the authors evaluated different scenarios, such as using only weather data, only intermediate variables prediction intervals, only SFP intervals, or all these variables together. They found that simulations incorporating all variables outperformed the others consistently.…”
Section: Residual Error Modelingmentioning
confidence: 99%
“…According to (Ashwin et al, 2018), their study deals with obtaining models of the rainfall precipitation by using Deep Learning Architectures (LSTM and ConvNet) and determining the better architecture and claiming that for any time series dataset, Deep Learning models will be effective and e cient for the modelers. (Roy et al,2023), the authors investigate the potential of a hybrid modeling framework that couples the random forest algorithm, particle lter, and the HBV model for improving the overall accuracy of forecasts at higher lead times through the dynamic error correction schematic. We can improve our understanding of natural resource dynamics and create e cient plans for their sustainable management by utilizing the capabilities of grid-based technologies and GIS.1.1.…”
mentioning
confidence: 99%